The Implementation of Stakeholder, Asymmetry, Signaling, and Agency Theories on the Determinant of Shariah Bond (Sukuk) Rating - Bedjo Santoso; Ibnu Qizam; Wan Noor Hazlina Wan Jusoh; Leonova Olga Viktorovna (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
The paper aims to develop a model of determinant of the Sukuk (Islamic/shariah bond) rating (SR) derived from four theories combined together include stakeholder, asymmetry, agency, and signaling theory by using synthesizing process resulted a new concept of variables which have been neglected by some researchers. The variables; GCG (good corporate governance), FDQ (quality of financial disclosure) ABRs (accounting based risks) EM (earning management), and FP (financial performance). This research is important in Indonesia as the largest Muslim country that is intensively building infrastructures. This study used 570 data panel annual reports. This study revealed that GCG and FDQ have positive influence on the SR whereas ABRs and EM have a negative effect on SR. However, EM fail to mediate ABRs to SR. In addition, FP did not succeed to mediate EM on SR as this related to moral hazard issue, but FP affect to SR. Direct effect GCG, FDQ, and ABRs to SR is greater than indirect effect these variables to SR through EM. It means stakeholders and asymmetry theory powerful to strengthen SR research. In this study, it was found some new issues in SR such as; minimizing conflict, governance, board of commissions, report quality, risk performance, hence, it contributes to body of knowledge in asymmetry, agency, and stakeholder theory.